Neuroblastoma: the association of anatomical tumour site, molecular biology and patient outcomes - Salim Adeline; Raitio Arimatias; Pizer Barry; Mullassery Dhanya; Losty Paul D (WILEY, 2022)
Background Numerous factors have been identified as carrying prognostic value in neuroblastoma (NB) and therefore incorporated in risk stratification of disease. Here, we investigate the association of anatomical site of NB with molecular biology and clinical outcomes.Methods A total of 117 patients with NB were studied over a 30-year period. Tumour location was confirmed with computed tomography/magnetic resonance imaging. Data on molecular biology were obtained as testing became available. Chi-squared, Fisher's exact test and Kaplan-Meier log-rank tests were used for statistical analysis.Results Tumour originated in the thoracic region (thoracic NB, TNB) in 15 patients (13%), adrenal gland (adrenal NB, ANB) in 88 patients (75%) and abdominal/paravertebral chain (paravertebral NB, PVNB) in 14 patients (12%). Overall survival (OS) for ANB was significantly lower (38%; P = 0.015). ANB cases were more frequently diagnosed at stage IV (69%; P = 0.001). MYCN amplification was noted in 33% of ANB cases and associated with lower OS (17% versus 62% MYCN non-amplified ANB; P = 0.01). The vast majority of TNB and PVNB were non-MYCN amplified (100% and 86%, respectively) and carried better prognosis (OS 86% and 83%, respectively). Forty-two percent of ANB cases were diploid and had lower OS (20% versus 71% hyperdiploid ANB; P = 0.079). TNB and PVNB were found to be mostly hyperdiploid (86% and 100%, respectively) with better OS (83% and 33%, respectively). Segmental chromosomal alterations had prognostic significance in those with PVNB (P = 0.03).Conclusion TNB tumours have better outcomes than adrenal tumours. This may be due to varied factors reported here including non-metastatic disease at presentation, non-amplification of the MYCN oncogene and overall favourable molecular biology characteristics.